Current Status and Future Prospects of Conventional Recording Technologies for Mass Storage Applications - Wang, Lei; Yang, Ci-Hui; Gai, Shan; Wen, Jing (Current Nanoscience, 2014)
The global digital data has increased at an unprecedented rate during the last decade due to the digitization service of every industry as well as the rapid development of information technology. It is therefore timely to enhance the areal density of the mainstream storage devices in order to meet the current storage demand. In this paper, the development history of three major families of storage devices that consist of magnetic hard disk, magnetic tape, and optical disc has been reviewed associated with their respective strength and weakness when utilized for mass storage applications. Several emerging technologies that are likely to expand the areal density of the conventional recording forms beyond the physical limits are subsequently discussed in each case. The perspectives of these three devices used as next generation data storage memory are also compared with each other in terms of the areal density roadmap. According to the comparison, hard disk that is dominating the current mass storage market will still be the favorite candidate for next-generation storage device due to its ultra-high capacity and low cost, particularly with the help of several advanced technologies such as heat assisted magnetic recording and bit patterned media. In spite of much lower capacity than hard disk today, magnetic tape has exhibited an ample margin for booming the storage capacity, and its high stability and flexible removability render it a promising contender for data backup application. The prospect of optical disc seems to be somewhat pessimistic because of the rather slow progress on its capacity and the fairly high cost per GB. It is likely that optical disc will be superseded by the mass storage devices provided that no more innovative technologies than near-field recording and holographic storage emerge in the future. However, the potential merits of optical disc like long life time and portability may offer optical disc a new application that stores important data securely for long term such as official document and government legislation.
Keywords: optical disc